2001
DOI: 10.1073/pnas.091110398
|View full text |Cite
|
Sign up to set email alerts
|

Complex mtDNA constitutes an approximate 620-kb insertion on Arabidopsis thaliana chromosome 2: Implication of potential sequencing errors caused by large-unit repeats

Abstract: Previously conducted sequence analysis of Arabidopsis thaliana (ecotype Columbia-0) reported an insertion of 270-kb mtDNA into the pericentric region on the short arm of chromosome 2. DNA fiber-based fluorescence in situ hybridization analyses reveal that the mtDNA insert is 618 ؎ 42 kb, Ϸ2.3 times greater than that determined by contig assembly and sequencing analysis. Portions of the mitochondrial genome previously believed to be absent were identified within the insert. Sections of the mtDNA are repeated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
144
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 35 publications
13
144
0
Order By: Relevance
“…The Arabidopsis nuclear genome contains nearly complete copies of the mitochondrial genome on chromosome 2 [41], and it has been possible to observe chloroplast-to-nucleus DNA transfers in current experiments (reviewed in [42]). These observations imply that direct organelle-to-nucleus DNA transfer is ongoing.…”
Section: Box 1 the Nature Of Organellar Dna Transfers To The Nucleusmentioning
confidence: 99%
“…The Arabidopsis nuclear genome contains nearly complete copies of the mitochondrial genome on chromosome 2 [41], and it has been possible to observe chloroplast-to-nucleus DNA transfers in current experiments (reviewed in [42]). These observations imply that direct organelle-to-nucleus DNA transfer is ongoing.…”
Section: Box 1 the Nature Of Organellar Dna Transfers To The Nucleusmentioning
confidence: 99%
“…Approximately 250 proteins encoded in the nuclear (nu) genome are needed just to maintain and express the few remaining mitochondrial genes (7). Mitochondrial sequences are frequently copied to the nuclear genomes (8)(9)(10), confirming that mechanisms for the transfer of mitochondrial genes to the nuclear genome are in place. A major, unresolved question in evolutionary biology is why not all mitochondrial genes have been transferred to the nuclear genome, and thus why the mitochondrial genome has been retained.…”
mentioning
confidence: 94%
“…In Arabidopsis thaliana, an insertion of 270-kb mtDNA was found in the pericentromeric region on the short arm of chromosome 2 (Lin et al 1999). DNA fiber-based FISH analyses revealed that the mtDNA insert is 620 kb, 2.3 times greater than that determined by contig assembly and sequencing analysis (Stupar et al 2001). This may be due to duplication of mitochondrial sequences.…”
Section: Satellite Dnas Are a Major Component Of Cucumis Centromeresmentioning
confidence: 99%